2021
DOI: 10.3390/healthcare9091110
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions of COVID-19 Vaccines: Policy Implications from US Spatiotemporal Sentiment Analytics

Abstract: There is a compelling and pressing need to better understand the temporal dynamics of public sentiment towards COVID-19 vaccines in the US on a national and state-wise level for facilitating appropriate public policy applications. Our analysis of social media data from early February and late March 2021 shows that, despite the overall strength of positive sentiment and despite the increasing numbers of Americans being fully vaccinated, negative sentiment towards COVID-19 vaccines still persists among segments … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…However, the Voronoi map (Theisen polygon) was utilized in only one study [23]. The contribution of 11 articles to the spatial analysis of COVID-19 vaccination was only limited to mapping [24][25][26][27][28][29][30][31][32][33][34]. Although most mapping studies disregarded time components, and used static presentation of data, temporal variations or transmission dynamics were mapped in [24,29,30,[35][36][37].…”
Section: Vaccine Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the Voronoi map (Theisen polygon) was utilized in only one study [23]. The contribution of 11 articles to the spatial analysis of COVID-19 vaccination was only limited to mapping [24][25][26][27][28][29][30][31][32][33][34]. Although most mapping studies disregarded time components, and used static presentation of data, temporal variations or transmission dynamics were mapped in [24,29,30,[35][36][37].…”
Section: Vaccine Mappingmentioning
confidence: 99%
“…In a spatiotemporal study, Ali et al [24] examined public perceptions of COVID-19 vaccines using choropleth maps. They found that fear sentiment remained unchanged in populous US states, whereas trust sentiment declined slightly in the same states.…”
Section: Vaccine Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, multiple new variants of the COVID-19 virus that transmit more readily from person to person and change the effectiveness of the vaccines are emerging and circulating in the US and around the world 10 . Additionally, people are hesitant to receive vaccine against COVID-19 infection in the US 11 . Thus, a combination of evidence-based pharmaceutical and non-pharmaceutical public health mitigation measures remains important to curtail viral transmission locally and beyond 12 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the overall strength of positive sentiment and the increasing number of Americans who are fully vaccinated, their analysis of social media data from early February to late March 2021 shows that negative sentiment toward COVID-19 vaccines persists among segments of people who are hesitant towards the vaccine. In this study, they have performed sentiment analytics on vaccine tweets, monitored changes in public sentiment over time, contrasted vaccination sentiment scores with actual vaccination data from the US CDC and the Household Pulse Survey (HPS), explored the influence of maturity of Twitter user-accounts and generated geographic mapping of tweet sentiments (Hossain et al, 2021).…”
mentioning
confidence: 99%